Formation of Pedagogical Skills of Future Teachers of Physical Culture in Classes on Sports Games - Mozolev, Oleksandr; Khmara, Maryna (Pedagogical Discourse, 2024)
The article explores the theoretical foundations of the formation of pedagogical skills of future physical education teachers. The aim is to reveal the content of the formation of pedagogical skills of future physical education teachers in sports games classes at the Khmelnytsky Humanitarian and Pedagogical Academy (KHPA). To solve the tasks set, we used general scientific and special research methods: theoretical analysis of educational and scientific literature; observation method; comparative method; comparative method; problem-oriented method. Results. It was established that the current model of the formation of pedagogical skills of future physical education teachers at the KhPA is focused on ensuring the comprehensive development of specialists, where theoretical knowledge is combined with practical skills and abilities, and the educational process is aimed at the formation of competencies that ensure the competitiveness of graduates in the labor market. The formation of theoretical knowledge and professional competencies of future physical education teachers at KhGPA occurs through the study of educational blocks in the following disciplines: pedagogy, psychology, morphofunctional and metabolic foundations of physical education, theory and methodology of physical education, inclusive physical education of schoolchildren. The relationship between theoretical and practical training of future physical education teachers at KhGPA is carried out in practical classes by conducting part of the class. In the formation of pedagogical skills of future physical education teachers, a significant place is given to the practical component, which provides for seven types of practice. Sports games classes most effectively allow developing the necessary professional skills, because it is in sports games classes that situations most often arise that require prompt, professional and correct intervention by the teacher. Sports and outdoor games for schoolchildren are an integral part of the educational process, therefore, an important place in the training of future physical education teachers is given to the formation of skills in organizing this type of activity.